Optimal design of curing process for manufacturing a high pressure hydrogen vessel (type 4) - Kang, Yeontae; Park, Gunyoung; Kwak, Hyoseo; Qi, Haonan; Kim, Chul (Journal of mechanical science and technology, 2023)
A type 4 pressure vessel is reinforced by a carbon fiber composite material on a polymer liner and is manufactured through a curing process hardening a viscous resin. During a curing process, strength degradation occurs due to residual stress, so it is recommended to cure for a long time, but a fast curing process has been required for high productivity. In this study, to solve these problems, the optimal design of curing process was performed for a hydrogen vehicle pressure vessel (type 4) made of carbon fiber (T700/epoxy) through FEA (finite element analysis). Autocatalytic kinetic model equation was derived through dynamic and isothermal DSC (differential scanning calorimeter) experiments by varying curing temperature. Thermal-static structural coupled analysis of composite curing process was conducted using ACCS (ANSYS composite cure simulation) program. The input parameters affecting curing process were assigned; curing temperature (T), heating rate to reach target curing temperature (H), dwell time to maintain the target temperature (D) and cooling time (C). Output parameters affecting delamination and process time were assigned; σ z , τ xz and total time (TT). 71 sampling points were generated, and design of experiments were conducted. Goodness of fit of response surface was generated to check its reliability. The optimum model, which satisfies the objective function, was suggested using MOGA algorithm. The thermal-static structural coupled analysis of final model was performed to verify the optimal design.